Hyers-ulam stability of certain class of nonlinear second order differential equations (2018)
We investigate the Hyers-Ulam stability of certain classes of nonlinear second order differential equations using a nonlinear generalisation of Gronwall-Bellman integral inequality known as Bihari integral inequality.